2003
DOI: 10.1103/physrevlett.90.216601
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Optically Injected Spin-Polarized Currents in Semiconductors

Abstract: Quantum interference of one- and two-photon excitation of unbiased semiconductors yields ballistic currents of carriers. The magnitudes and directions of the currents and the spin orientations of the carriers are controlled by the polarization and relative phase of the exciting femtosecond laser fields. We provide direct experimental evidence for the spin polarization of the optically injected spin currents by detecting a phase-dependent spatial shift of the circularly polarized photoluminescence in cubic ZnSe. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
152
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(156 citation statements)
references
References 12 publications
1
152
3
Order By: Relevance
“…Murakami et al 4 and Sinova et al 5 have shown that an in-plane electric field can cause a spin current, leading to the "intrinsic spin-Hall effect". Another possibility for the injection of spin current is coherently controlled optical excitations between the valence and the conduction band, as predicted by Bhat and Sipe 6,7 and observed experimentally in bulk crystals 8,9 and quantum wells (QWs) 10 .…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Murakami et al 4 and Sinova et al 5 have shown that an in-plane electric field can cause a spin current, leading to the "intrinsic spin-Hall effect". Another possibility for the injection of spin current is coherently controlled optical excitations between the valence and the conduction band, as predicted by Bhat and Sipe 6,7 and observed experimentally in bulk crystals 8,9 and quantum wells (QWs) 10 .…”
mentioning
confidence: 94%
“…Another possibility for observing the pure spin current is spatially resolved pump-probe spectroscopy, as applied by Hübner et al 9 and Stevens et al 10 to investigate the spin current injected by interband transitions. In those experiments the centers of the spin-up and spin-down of excited electron distribution were separated by approximately 20 nm.…”
mentioning
confidence: 99%
“…Based on the spin pumping principle, 8,9 an alternating or inhomogeneous magnetic field as a spinpumping force could result in a pure spin current. Experimentally, Stevens et al 10 and Hubner et al 11 have independently realized the pure spin current by using the quantum interference of two-color laser fields with cross-linear polarization in ZnSe and GaAs semiconductors. The transport of spin current by magnons have been theoretically studied by several groups, 12-14 e.g., Meier et al 12 demonstrated that by using a finite length spin chain between magnetic reservoirs, pure spin current can be generated without the transport of electrical charge.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interband '1 + 2' interference in unbiased semiconductors, which is our interest here, allows independent control of electrical current injection 11,12 and spin current injection. 13,14,15,16,17,18 Furthermore, in noncentrosymmetric semiconductors, it allows independent control of carrier populations (i.e., absorption) 19,20 and carrier spin polarization. 21, 22 In each scenario, the experimenter can control the interference by adjusting the phases of the two colors.…”
Section: Introductionmentioning
confidence: 99%